Synthesis, characterization, antioxidant, antimicrobial, DNA binding and cleavage studies of mononuclear Cu(II) and Co(II) complexes of 3-hydroxy-N'-(2-hydroxybenzylidene)-2-naphthohydrazide - Kumar, Linganna Shiva; Prasad, Kollur Shiva; Revanasiddappa, Hosakere Doddarevanna (European Journal of Chemistry, 2011)
In this report, we explore the DNA binding properties of mixed ligand copper(II)/cobalt(II) complexes of the type [M(bnp)(phen)H2O].nH2O, and copper(II)/cobalt(II) complexes of the type [M(Hbnp)2], where n=0, 1, ..., H2bnp=3-hydroxy-N'-(2-hydroxybenzylidene)-2-naphtho-hydrazide and phen=1,10-phenanthroline. A host of physical methods like spectral absorption, emission studies and hydrodynamic measurements have been used to probe the effect of ligands on the mode and extent of interaction of the complexes with Calf Thymus DNA. The efficiencies of the complexes to oxidatively cleaved pUC19 DNA was performed in the absence and presence of H2O2. Among the compounds tested for antioxidant capacity, H2bnp displayed excellent activity than its complexes and standards used. It has been observed that Cu(II) and Co(II) complexes exhibited different levels of antibacterial and antifungal effects, with the assays carried out on four pathogenic bacteria and two pathogenic fungi. H2bnp showed moderate activity against bacteria E. coli, X. vesicatoria and fungi, A. niger and A. flavus, but less than its complexes and standard drugs used for assay.